Effectiveness of Video and Leaflet Educational Media in Increasing Adolescent Mental Health Literacy - Sutiawati, Dewi Nur; Suitini, Titin; Fauziah, Munaya; Purwati, Nyimas Heni; Nuraidah, Nuraidah (Jurnal Keperawatan, 2024)
Mental health determines the well-being of adolescents, because adolescence is a time when major changes occur in the body, psychology and society. Mental health literacy is important to increase the capacity of adolescents to face unexpected challenges, for this reason education is needed to increase literacy. Delivering education requires interesting media so that information can be conveyed well, video media and leaflets can be used as educational media. The aim of this research is to determine the difference influence of video and leaflet-based on education of adolescent mental health literacy at Bintang Harapan Vocational School Bekasi. This research design uses a two-group pretest-posttest design without control. The sample for this research was taken using proportionate stratified random sampling with a total of 210 adolescents who were divided into105 adolescents ach in the video and leaflet education groups. Mental health literacy was measured using the MHL-q (Mental Health Literacy-Questionnaire) questionnaire. Data analysis used the independent t-test. The results of the research show that there is no difference in the effect of video and leaflet interventions on adolescent mental health literacy with p value = 0.253 (p> 0.005), so it can be concluded that video and leaflet-based education are equally influential in increasing adolescent mental health literacy. Confounding factors that influence adolescent mental health literacy are gender and access to information. It is recommended that video and leaflet educational media can be used as health education media, especially to increase mental health literacy in adolescents.